Design of Ni(OH)2/M-MMT Nanocomposite With Higher Charge Transport as a High Capacity Supercapacitor - Xu, G. M.; Wang, M.; Bao, H. L.; Fang, P. F.; Zeng, Y. H.; Du, L.; Wang, X. L. (Frontiers in Chemistry, 2022)
Nano-petal nickel hydroxide was prepared on multilayered modified montmorillonite (M-MMT) using one-step hydrothermal method for the first time. This nano-petal multilayered nanostructure dominated the ion diffusion path to be shorted and the higher charge transport ability, which caused the higher specific capacitance. The results showed that in the three-electrode system, the specific capacitance of the nanocomposite with 4% M-MMT reached 1068 F/g at 1 A/g and the capacity retention rate was 70.2% after 1000 cycles at 10 A/g, which was much higher than that of pure Ni(OH)2 (824 F/g at 1 A/g), indicating that the Ni(OH)2/M-MMT nanocomposite would be a new type of environmentally friendly energy storage supercapacitor.